Advanced atrioventricular block and left bundle branch block in a patient with coronary artery fistula. Issue 12 (22nd December 2020) - Ono, Ryohei; Okada, Sho; Kitagawa, Mari; Takaoka, Hiroyuki; Miyauchi, Hideyuki; Kobayashi, Yoshio
Abstract : Coronary artery fistulas are abnormal vascular conduits, rarely related to atrioventricular conduction abnormalities. We report the case of a 52-year-old woman who presented with dyspnoea on exertion. Her ECG revealed advanced atrioventricular block and left bundle branch block. CT scans confirmed two fistulas, from the conus branch of right coronary artery and from the left anterior descending coronary artery, into the pulmonary artery. The patient underwent pacemaker implantation. To date, only nine patients with different degrees of heart blocks associated with coronary artery fistulas have been reported. Herein, we review and summarise previously reported cases of different degrees of heart blocks associated with coronary artery fistulas.